Pengaruh Teknik Kompres Dingin Terhadap Intensitas Nyeri Dismenore Primer Pada Remaja Putri Di SMP Negeri 31 Padang - Viki Yusri; Rini Rahmayanti; Febriyanti (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2023)
The incidence of dysmenorrhea in 2016 is very high, it is estimated that more than 50% of women in the world feel this condition, in Indonesia 2020 the incidence of dysmenorrhea is 64,25% and in West Sumatra 2016 it is 57,3%. Interventions that can be given to overcome the intensity of dysmenorrhea pain are cold compresses. The purpose of this study was to determine the effect of the cold compress technique on the intensity of dismenorrhea pain in adolescent girls at SMP Negeri 31 Padang. This type of research uses a pre-experimental researh design with a one-group pretest and posttest design. A sample of 15 respondents with a sampling technique that is purposive sampling. The data processing used in this research is the T-test. The result showed that the average intensity of primary dysmenorrhea pain before the cold compress intervention was 7.00 and the average after the cold compress intervention was 3,47 with p velue= 0,000 (p<0,05), meaning that there was an effect of cold compress technique on intensity of primary dysmenorrhea pain in adolescent girls at SMP Negeri 31 Padang. The conclusion of this study is that there is an effect of cold compress technique on the intensity of primary dysmenorrhea pain in adolescent girls at SMP Negeri 31 Padang. It is recommended for respondents to use cold compresses as an intervention if the pain of dysmenorrhea.